Field evalution of fungicides against fungi causing discolouration of paddy seeds - DHARAM VIR, A. K. MISRA* and (Indian Phytopathology, 2002)
Five fungicides, viz., validacin (antibiotic) (200 ppm), vitavax (0.25%), captan (0.25%), thiram (0.25%) and bavistin+ thiram (formulated) (0.25%) were tested in field against the fungi causing seed discolouration of paddy. The fungicides were applied on panicles at milk stage as pre-inoculation and post-inoculation sprays at two days interval. None of the fungicides provided complete control of seed discolouration. However, partial control was achieved. In general. pre-inoculation fungicides application was found superior 10 post-inoculation fungicides application.